The Question Concerning Design - Erdman, Jori (ARCC Conference Repository, 2014)
The American Heritage Dictionary defines design as both a verb and a noun with the general meaning that someone makes and/or executes plans or the actual plans. However, many disciplines claimto design as a part of their productivity and result of their labor. The problem comes when these disciplines and professions work collaboratively. Their individual understandings of the term "design” can lead to much confusion and misunderstandings amongst team members. Since so much design is interdisciplinary and collaborative, this is becoming more and more of issue. I am currently working in an environment with architects, engineers and scientists who are coming together to "design” a project but we are coming at this from very different understandings of the term.This paper will attempt to unpack the meaning and practice of design for the disciplines of architecture, engineering and science. I will employ the comparative method to examine the way that architects, engineers and scientists use this word to describe what they do in order to discover the similarities and differences of usage. The paper will begin with a look at the etymology of the word, ”design,” and then will provide an overview of the literature and practices available on the topic of design for each discipline. The intent is to find a common ground between the disciplines or at least provide a lexicon for the disciplines when working together